CD49a promotes T‐cell‐mediated hepatitis by driving T helper 1 cytokine and interleukin‐17 production. Issue 3 (March 2014) - Chen, Yonglin; Peng, Hui; Chen, Yongyan; Wei, Haiming; Sun, Rui; Tian, Zhigang
Summary It is becoming increasingly clear that the T‐cell‐mediated immune response is important in many diseases. In this study, we used concanavalin A (Con A) ‐induced hepatitis to investigate the role of CD49a in the molecular and cellular mechanism of the T‐cell‐mediated immune response. We found that CD49a−/− mice had significantly reduced levels of serum alanine aminotransferase and were protected from Con A‐induced hepatitis. CD49a deficiency led to decreased production of interferon‐γ (IFN‐γ) and interleukin‐17A (IL‐17A) after Con A injection. Furthermore, we found that hepatic CD4+ T cells and invariant natural killer T cells up‐regulated CD49a expression, along with enhanced activation after Con A injection, leading to production of inflammatory cytokines by these T cells. Blockade of CD49a in vivo ameliorated Con A‐induced hepatitis with reduced production of IFN‐γ and IL‐17A. Hence, CD49a promoted Con A‐induced hepatitis through enhancing inflammatory cytokine production (IFN‐γ and IL‐17A) by CD4+ T and invariant natural killer T cells. The protective effect of CD49a blockade antibody suggested a new target therapeutic molecule for intervention of T‐cell‐mediated liver injury.